Molecular identification of coprophilous microfungi from Banyumas District, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mumpuni A, Amurwanto A, Wahyono DJ. 2021. Molecular identification of coprophilous microfungi from Banyumas District, Central Java, Indonesia. Biodiversitas 22: 1550-1557. Coprophilous microfungi are a group of fungi that are ecologically interesting in relation to herbivores. These fungi play a predominant role in the decomposition of organic matter, in which the organic matter passes through a series of events involving mechanical degradation, as well as physical and biological processes. The role of coprophilous fungi as the main decomposers of the lignocellulosic material of herbivorous animal waste, which is widespread in nature, is very important. Previous research on the inventory and identification of coprophilous fungi in the Banyumas district has been limited to macroscopic genera, so the results have not been able to provide a comprehensive picture of the presence of coprophilous fungi in the region. Identification of the types of microscopic coprophilous fungi that live in herbivorous animal waste, such as lignocellulosic material, is necessary to understand the taxonomy of these fungi. This study aimed to investigate and identify microscopic coprophilous fungi obtained in the Banyumas district of Central Java, Indonesia. Based on the purposive random sampling method, the obtained fungi were analyzed using the molecular methods of DNA isolation, gene amplification, DNA sequencing and phylogenetic analysis of fungal cultures. The following species and genera were identified: Ceriporia lacerata, Trichosporon insectorum, Lentinus squarrosulus, Fusarium sp., Aspergillus sp., and Trichosporon sp.
Keywords: coprophilous fungi, inventory, molecular identification